Material Educativo Computarizado (MEC), para la enseñanza de Zoologia Cordados y su aplicación en el Programa de Licenciatura en Biología y Educación Ambiental de la Universidad del Quindío. (2016)
This research had as main objective the design and implementation of a computerized educational materials (CEM) for the course of chordate zoology degree program in Biology and Environmental Education at the University of Quindío, looking at the process that students assimilate the concepts contained in the material, during the methodological process we worked with the group of chordate zoology with which it conducted two surveys, in the first survey or pre-analysis was sought and discuss the concepts prior to the use of educational material, these results were compared with a post analysis made looking the benefits of using an educational material as a reference tool. The results obtained with the experience of teaching – learning were satisfactory finding a significant improvement in each of the concepts evaluated of the topics covered in the course and also achieved a greater interest in research by students since this type of new teaching methods invite further enrich the knowledge about the subjects studied. It was concluded that the use of an MEC as a reference tool increases interest and knowledge acquired in the classroom by the students encouraging the use of technologies and further increasing the academic level in group strengthening and encouraging research in the academy.